To find the y-intercept of Function A, we rearrange the equation \(4x - 3y = 12\) to the slope-intercept form \(y = mx + b\):
\[ -3y = -4x + 12 \ y = \frac{4}{3}x - 4 \]
The y-intercept of Function A is \(-4\).
Next, we can find the slope of Function A, which is \(\frac{4}{3}\).
Now, let's find the slope of Function B using the points (4, 1) and (8, 4). The slope \(m\) is calculated as follows:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{4 - 1}{8 - 4} = \frac{3}{4} \]
Now we have all the necessary information:
- The y-intercept of Function A is \(-4\).
- The slope of Function A is \(\frac{4}{3}\).
- The slope of Function B is \(\frac{3}{4}\).
Now we can complete the paragraph:
The y-intercept of Function A is less than the y-intercept of Function B. The slope of Function A is greater than the slope of Function B.
Answer:
The y-intercept of Function A is less than the y-intercept of Function B. The slope of Function A is greater than the slope of Function B.